The earliest Acheulean at Kokiselei 4, West Turkana, Kenya - (:unkn) unknown (My University, 2023)
This handbook showcases an Africa-wide compendium of Stone Age archaeological sites and methodological advances that have improved our understanding of hominin lifeways and biogeography in the continent. The focal time spans the Pleistocene Epoch (c. 2.5 million–11,700 years ago) during which important human traits, such as obligate bipedalism that freed the hands to engage in creative activities, a large brain relative to body size, language, and social complexity, developed in the general forms that they are found today.
Keywords: African Research